A Study of Student Teachers’ Blackboard-Use Ability in Mathematics Classrooms Implementing Lesson Study and Open Approach - Rujirawinitchai, Tidarat; Kanauan, Weerasuk (Education journal Faculty of Education, Nakhon Sawan Rajabhat University, 2025)
This action research aimed to investigate the blackboard utilization abilities of pre-service mathematics teachers in classrooms implementing Lesson Study and Open Approach, based on the framework of Inprasitha (2011). The target group consisted of 20 mathematics education students from a faculty of education at a university in Ubon Ratchathani Province, selected through purposive sampling. Data were collected using participant observation with an observation form, video and images recordings, interviews, and document analysis. The data were analyzed using content analysis, along with descriptive statistics such as percentage and mean to describe students’ levels of blackboard use based on Yoshida’s (2004) framework. The findings revealed that the students' blackboard usage aligned with the instructional phases of the Open Approach and showed progressive development from level 2 to level 4. According to the action research cycles, most students began at level 1 in the first cycle (75%), progressed to level 2 in the second cycle (65%), and significantly advanced to levels 3 and 4 in the third cycle (65% and 20%, respectively). These results indicate a continuous improvement in their ability to effectively use the blackboard.